2019
DOI: 10.23736/s0026-4954.18.01829-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of individualized aerobic threshold-based exercise on ventilatory efficiency in sedentary adult asthma patients

Abstract: Background: The aim of this trial was to assess the feasibility of the future definitive study that will define the effects of aerobic threshold based exercise on ventilatory efficiency in sedentary adult female asthma patients. Methods: Six female asthma patients performed an individualized aerobic training program for 7 weeks with their ventilatory parameters measured before and after exercise intervention using breath-by-breath gas analysis and graded treadmill test until volitional exhaustion. Paired sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…Frequency of training was reported in all but two studies51,78 and was generally described as sessions/wk or d/wk. Frequency ranged from 148 to 1249 sessions/wk, with 3 sessions/wk being the most common prescription (n = 18 studies) 35,36,40,42,44–46,50,51,53–58,61,63,64,70. Candemir et al60 prescribed training 5 d/wk for participants, with 3 d designated for aerobic exercise and 2 d designated for resistance exercise.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Frequency of training was reported in all but two studies51,78 and was generally described as sessions/wk or d/wk. Frequency ranged from 148 to 1249 sessions/wk, with 3 sessions/wk being the most common prescription (n = 18 studies) 35,36,40,42,44–46,50,51,53–58,61,63,64,70. Candemir et al60 prescribed training 5 d/wk for participants, with 3 d designated for aerobic exercise and 2 d designated for resistance exercise.…”
Section: Resultsmentioning
confidence: 99%
“…60 Only four studies reported measures of muscular fitness 49,58,68,69,77 including 1RM testing, 68 dynamometers, 49,58 or manual muscle testing. 77 Measures of HRPF reported in addition to one of the above outcomes included resting/submaximal HR, 35,42,61,62,66,67 anaerobic threshold, [43][44][45]50 peak ventilation, 35,42,45,48 and peak workload. 35,41,46,48,51,53…”
Section: Health-related Physical Fitness Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations